Front Cover: Formation and Surface Behavior of Pt and Pd Complexes with Ligand Systems Derived from Nitrile‐functionalized Ionic Liquids Studied by XPS (ChemPhysChem 2/2023). Issue 2 (17th January 2023) - Hemmeter, Daniel; Paap, Ulrike; Taccardi, Nicola; Mehler, Julian; Schulz, Peter S.; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans‐Peter
Abstract : The Front Cover shows substitution of volatile acetonitrile ligands by a nitrile‐functionalized imidazolium cation. The formed cationic complex and the counter ions exhibit a specific preferential orientation at the ionic liquid/gas interface, which can be studied by angle‐resolved XPS. More information can be found in the Research Article by Hans‐Peter Steinrück and co‐workers .